Penguatan Literasi Digital bagi Kader Posyandu Margosari untuk Optimalisasi Pemantauan Kesehatan Balita - Dodi Zulherman; Tenia Wahyuningrum; Sevia Indah Purnama; Nathanael Andra Wijaya; Anggun Dewanti; Muhammad Nabil Irfanurhalim; Fakhir Mustafa Afdal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Posyandu (Community-Based Integrated Health Service Post) has played a pivotal role in reducing morbidity and mortality rates among infant and toddler in Indonesia over several decades. In alignment with this role, posyandu has been integrated as a community health service for all age groups, from infants to elderly, over the past years. However, despite its critical importance, posyandu operations have not kept pace with modernization; most recording, reporting, and archiving activities are still conducted manually. This conventional approach is prone to errors, loss of records, and limited data accessibility. Implementing online-based services, such as those offered by Google, presents a viable solution for digital transformation at every stage of posyandu operations. This program aims to enhance the digital literacy of posyandu cadres to improve the efficiency of health data recording in Ledug, Kembaran District, Banyumas Regency. By doing so, it seeks to create a more reliable system capable of minimizing errors, preventing data loss, and ensuring flexible access. The program was structured into three phases: preparation, implementation, and evaluation. Thirteen cadres participated in the activities conducted between April and May 2025. Evaluation results indicated improvements in both digital understanding and the implementation of digital tools within posyandu operations, with increases of 14.3% and 4.3%, respectively. Participants also rated the program's effectiveness at 3.24 out of 4, reflecting a high level of satisfaction. These indicators suggest that the training effectively enhanced the digital literacy of the cadres, with the expectation that this knowledge will be applied in the services provided at Posyandu Margosari.